tRNA-derived small RNAs (tsRNAs) in cardiovascular diseases: biogenesis, functions, and therapeutic targets - Xie, Chunfeng; Chen, Sihong; Wang, Chengyuan; Si, Wei; Wang, Zidan; Luo, Qi; Qi, Chan (Frontiers in Cardiovascular Medicine, 2025)
tRNA-derived small RNAs (tsRNAs) are a class of non-coding RNAs that are generated by cleavage of precursors or mature tRNAs under stress conditions such as hypoxia, oxidative stress and nutrient deficiency. Recent breakthroughs in RNA sequencing technology have revealed their association with cardiovascular diseases (CVDs), including myocardial infarction (MI), atherosclerosis, cardiac hypertrophy, aortic coarctation, and pulmonary arterial hypertension. tsRNAs play important biological functions in these diseases, including the inhibition of apoptosis, epigenetic modification, intercellular signaling mediation, translation, and regulation of gene expression. In addition, tsRNAs show promise as both detectable indicators and intervention targets for CVD. This review examines the biogenesis, classification, and multifaceted functions of tsRNAs in CVD, emphasizing their dual roles as diagnostic tools and therapeutic targets. future research should focus on elucidating tsrna-mediated regulatory networks and developing RNA-based interventions to address unmet needs in cardiovascular medicine.